Active surveillance for non-muscle-invasive bladder cancer: fallacy or opportunity?. Issue 5 (22nd September 2022) - von Deimling, Markus; Pallauf, Maximilian; Bianchi, Alberto; Laukhtina, Ekaterina; Karakiewicz, Pierre I.; Rink, Michael; Shariat, Shahrokh F.; Pradere, Benjamin
Abstract : Purpose of review: This review aims to analyze the current place of active surveillance (AS) in non-muscle-invasive bladder cancer (NMIBC). Recent findings: A growing body of evidence suggests that AS protocols for pTa low-grade (TaLG) NMIBC are safe and feasible. However, current guidelines have not implemented AS due to a lack of high-quality data. Available studies included pTa tumors, with only one study excluding pT1-NMIBC. Inclusion/exclusion criteria were heterogeneously defined based on tumor volume, number of tumors, carcinoma in situ (CIS), or high-grade (HG) NMIBC. Tumor volume <10 mm and <5 lesions were used as cut-offs. Positive urinary cytology (UC) or cancer-related symptoms precluded inclusion. Surveillance within the first year consisted of quarterly cystoscopy. AS stopped upon the presence of cancer-related symptoms, change in tumor morphology, positive UC, or patient's request. With a median time on AS of 16 months, two-thirds of the patients failed AS. Progression to muscle-invasive bladder cancer (MIBC) was rare and occurred only in patients with pT1-NIMBC at inclusion. Summary: AS in NMIBC is an attractive concept in the era of personalized medicine, but strong evidence is still awaited. A more precise definition of patient inclusion, follow-up, and failure criteria is required to improve its implementation in daily clinical practice.